Menakar Efektivitas Konseling Individual dan Kelompok: Implikasi bagi Praktik Bimbingan dan Konseling - Sufiandi, Adhelia Caroline; Soviana, Amelia Fauziyyah; Rakhmadiana, Dieni Nur Ilmi Fauziah; Rahmadhani, Rizky; Putri Malinda, Syifa'ul Ummah Salsabila (JURNAL KONSELING GUSJIGANG, 2024)
This research discusses face-to-face counseling services, both individually and in groups, as a strategic approach to support individual personal, social and academic development. Individual counseling provides personalized attention to address clients' specific problems, while group counseling utilizes social dynamics to create shared learning and improve interpersonal skills. This study uses a qualitative approach with descriptive analysis methods to compare the effectiveness of these two types of services based on literature and empirical findings. The results of the analysis show that individual counseling is more effective in dealing with personal and deep-seated problems, while group counseling is superior in building social support and improving participants' social and emotional skills. In addition, these two approaches have integration that can be optimized in guidance and counseling practices to improve individual psychological well-being. The implications of this research highlight the importance of selecting a counseling approach that suits the client's needs and characteristics in order to achieve optimal results.